Let-7f-5p suppresses Th17 differentiation via targeting STAT3 in multiple sclerosis - Li, Zhi-Hui (Aging (Albany NY), 2019)
T helper 17 (Th17) cells are regarded as key factors in the pathogenesis of multiple sclerosis (MS). Although the involvement of certain microRNAs (miRNAs) in the development of MS has been reported, their roles in Th17 cell differentiation and MS pathogenesis remain elusive. In this study, we identified that let-7f-5p expression is significantly downregulated in CD4(+) T cells from MS patients and during the process of Th17 differentiation. The overexpression of let-7f-5p suppressed Th17 differentiation, whereas the knockdown of let-7f-5p expression enhanced this progress. We then explored the molecular mechanism through which let-7f-5p suppressed Th17 differentiation and identified signal transducer and activator of transcription 3 (STAT3), a pivotal transcription factor of Th17 cells, as a direct target of let-7f-5p. In contrast to the downregulated expression of let-7f-5p, STAT3 and p-STAT3 protein levels were dramatically upregulated and inversely correlated with let-7f-5p in peripheral blood CD4(+) T cells from MS patients. In conclusion, let-7f-5p functions as a potential inhibitor of Th17 differentiation in the pathogenesis of MS by targeting STAT3 and may serve as a new therapeutic target.